The professional competence of teachers of higher educational institutions (Pedagogy of Higher and Secondary Education, 2012)
Skorobogatova M. The professional competence of teachers of higher educational institutions.Not enough the modern teacher of higher educational establishment to have only knowledges in certain subject domain, even high-level. For forming of professional competence permanent self-perfection and samorazvitie is needed. Application of kompetentnostnogo approach will let to carry out development of methodology and criteria of estimation of quality of preparation of teachers of institutes of higher.
Keywords: competence; professional competence; pedagogical competence